The application of Great Lakes ecosystem - based science to the restoration of the Gulf: A successful case study. Issue 2 (2nd April 2020) - Munawar, M.; Fitzpatrick, M.; Munawar, I.F.
Abstract : The Gulf (or Persian Gulf) suffers from multiple anthropogenic stressors relating primarily to its position as the centre of the global oil industry. Environmental degradation including oil spills, loss of coastal habitat, algal blooms and invasive species is evident but finding the right approach to address such degradation is challenging. The North American Great Lakes faced (and continues to face) similar challenges. The governments of Canada and the United States signed the Great Lakes Water Quality Agreement (GLWQA), which committed both countries to take concrete actions to protect the lakes. The GLWQA also offered a management framework called the Ecosystem Approach to deal with existing as well as emerging threats. A similar commitment to protect the Gulf, and more importantly the people who depend on it for their livelihood, is essential.